PENGARUH PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN DAN REPURCHASE MELALUI TRIAL PADA SOGO DEPARTMENT STORE DI KOTA SURABAYA - DEWI, YOVITA ANDIKA (Kajian Ilmiah Mahasiswa Manajemen, 2013)
The Intense competition among retailers require them to establish an attractive sales promotion strategy. Sales promotion strategies can be directed to support strong consumer buying decisions. The appeal of the sales promotion strategy depends on how big the benefits obtained by consumers. when benefits gained high consumer adoption sales promotion strategies to be followed by the high buying decisions. Based on the sales promotion program of excellence set by retailers, encouraging consumers to try (trial) the purchase decision made. Initially consumers are not interested in visiting a store, but with the promotion program to support consumer traffic and consumers interested in making a purchase. Consumer purchase decisions through a process and are the evaluation of various alternatives. Various alternatives menjai consideration for purchase. In the long term, the trial purchases that consumers can continue because consumers already feel comfortable when shopping in a store.